Sistem Pemesanan Makanan Menggunakan Qr di Restoran Nuansa By Lawa Berbasis Web dan Mobile - Nusi, Aril; Mohidin, Ismail; Hermawanto, Fajar (JURNAL TEKNIK INFORMATIKA, 2025)
In the digital era, QR code-based technology is an innovative solution for improving operational efficiency and service quality in restaurants. This research aims to design a web-based food ordering system with a QR code menu for dine-in services. This system allows customers to order food independently through a digital menu, equipped with real-time order management features and payment integration through the cashier. With this system, restaurants can reduce recording errors, waiting times, and staff workload, while increasing customer convenience, service efficiency, and competitiveness in the culinary industry.